FRANCISCO SALZIILLO Y LA ESTÉICA NEOCLÁSICA - Ramallo Asensio, Germán (Imafronte, 1999)
Starting from a formal analysis of some of Salzillo’s later works, and comparing them with others of similar themes produced in his early or middle years, this paper attempts to demonstrate the sculptor’s closeness to the neo-classical aesthetic. This artistic stance is considered as voluntary and conscious. It is justified by the favorable prevailing conditions that the city of Murcia enjoyed in the 18th century, especially in this last third by Salzillo’s inlellectual milieu, the connections with the court and finally his own acodemic formation. This last aspect is shown by the numerous sketches he used, his knowledge of other engravings of famous works. and his the crearion of a personal academy in which inherent problems of the Arts and new artistic trends were keenly debated.